Exploring the Therapeutic Potential of 1,3-Thiazole: A Decade Overview - Manchare, Ajit; Parit, Swapnali; Lele, Mukta; Hatvate, Navnath (Medicinal Chemistry, 2025)
The escalating prevalence of lifestyle and microbial diseases poses a significant threat to human well-being, necessitating the discovery and development of novel drugs with distinct modes of action. Addressing this challenge involves employing innovative strategies, and one current approach involves utilizing heterocyclic compounds to synthesize hybrid molecules. These hybrids have resulted from the fusion of two or more bioactive heterocyclic moieties into a single molecule. The focus of this review revolves around the strategic incorporation of heterocycles, particularly thiazole derivatives. Thiazole derivatives, due to their unique structural features, are explored in depth within this review paper. The paper comprehensively outlines diverse hybridization strategies of thiazole derivatives, highlighting their vibrant biological activities mainly in the last decade, 2014-2024. By presenting an extensive overview, the review aims to provide valuable insights into the potential of thiazole derivatives as promising candidates for drug development. The insights garnered from this paper are expected to offer valuable guidance for future drug design endeavors, providing a foundation for developing novel and effective drugs to combat lifestyle diseases and microbial resistance.
Keywords: anti-cancer agents